Sintering effects of mullite-doping on mechanical properties of bovine hydroxyapatite - OKTAR, FAİK NÜZHET; ERKMEN, ZİYA ENGİN (ELSEVIER SCIENCE BV, 2017)
In this study, sintering effects on microstructural behavior of bovine derived hydroxyapatite doped with powder mullite are considered in the temperature range between 1000 C-omicron and 1300 C-omicron. Results show that maximum values of both compressive strength and microhardness are achieved in the samples sintered at 1200 C-omicron for all mullite additions of 5, 7.5, 10 and 12.5 wt. Moreover, above 1000 C-omicron, decomposition of HA and new phase formations such as whitlockite and gehlenite play a major role in both compressive strength and microhardness properties which increase up to 10 wt mullite reinforcement. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Sintering; Mechanical properties; Bovine derived hydroxyapatite; Mullite; PHASE-STABILITY; COMPOSITES; SHELLS; BHA; POWDERS